Cardioprotective effect of ornitho-kinin in an anesthetized, open-chest chicken model of acute coronary occlusion - Prezoto,B.C. (2009)
The generation of bradykinin (BK; Arg-Pro-Pro-Gly-Phe-Ser-Pro-Phe-Arg) in blood and kallidin (Lys-BK) in tissues by the action of the kallikrein-kinin system has received little attention in non-mammalian vertebrates. In mammals, kallidin can be generated by the coronary endothelium and myocytes in response to ischemia, mediating cardioprotective events. The plasma of birds lacks two key components of the kallikrein-kinin system: the low molecular weight kininogen and a prekallikrein activator analogous to mammalian factor XII, but treatment with bovine plasma kallikrein generates ornitho-kinin [Thr6,Leu8]-BK. The possible cardioprotective effect of ornitho-kinin infusion was investigated in an anesthetized, open-chest chicken model of acute coronary occlusion. A branch of the left main coronary artery was reversibly ligated to produce ischemia followed by reperfusion, after which the degree of myocardial necrosis (infarct size as a percent of area at risk) was assessed by tetrazolium staining. The iv injection of a low dose of ornitho-kinin (4 µg/kg) reduced mean arterial pressure from 88 ± 12 to 42 ± 7 mmHg and increased heart rate from 335 ± 38 to 402 ± 45 bpm (N = 5). The size of the infarct was reduced by pretreatment with ornitho-kinin (500 µg/kg infused over a period of 5 min) from 35 ± 3 to 10 ± 2% of the area at risk. These results suggest that the physiological role of the kallikrein-kinin system is preserved in this animal model in spite of the absence of two key components, i.e., low molecular weight kininogen and factor XII.